FOREIGN EXPERIENCE IN ATTRACTING FOREIGN INVESTMENTS INTO THE NATIONAL ECONOMY (American Journal of Interdisciplinary Research and Development, 2023)
The article examines the role and importance of foreign investment in the socio-economic development of the country, studied international experience in attracting foreign investment into the national economy, and considered conclusions, proposals and recommendations based on international experience.